Insuring the safety of foods derived from nutritionally-enhanced plants and animals - Chassy, B.M. (Malaysian Society of Animal Production, 2015)
In recent years, the techniques of molecular biology - often called biotechnology - have been used by plant breeders to produce new transgenic plant varieties. These new varieties are intended to improve agricultural yields and/or profitability by conferring resistance to insects and viruses, or tolerance to herbicides. New plant varieties developed through biotechnology have been subjected to rigorous pre-market scientific review by government regulators prior to commercialization. The safety assessment strategy applied to transgenic crops is called the Substantial Equivalence paradigm. Almost all of the new crop varieties in use today are intended to produce commodities that are indistinguishable from their conventional counterparts with regard to safety, functionality and composition. Although their introduction has not been without controversy, these new varieties are planted each year on hundreds of millions of hectares around the world. Agricultural biotechnologists are currently developing food and feed plants with improved nutritional characteristics. Research is also being directed at the production of nutritionally enhanced transgenic animals. These crops and animals will by design have altered chemical composition and nutrient value. It is therefore necessary to determine if the safety assessment principles that were applied to the first commercial transgenic crops can be applied to these new non-equivalent varieties. This paper explores the applicability of the Substantial Equivalence paradigm and a multi-factorial food safety assessment process to nutritionally-enhanced crops. Recently, the International Life Sciences Institute (ILSI) has published a paper that reviews the applicability of present day assessment principles to these new crops. The authors conclude that the Substantial Equivalence paradigm is applicable and no new or unusual safety issues are presented by nutritionally-enhanced crops and animals.